O CAMINHO DO CORDEIRO: REPRESENTAÇÃO E CONSTRUÇÃO DE IDENTIDADE EM APOCALIPSE 14.1-5 - Miranda, Valtair Afonso (2010)
The analysis of Revelation 4.1-5 has disclosed several assertions that portrays the identity of John and his audience as well as the way they conceived the world. In their liturgical elements these people saw themselves as God s priests, members of His Kingdom, participants of His celestial worship with the same exalted dignity of the angels in heaven. However, some of these identifying elements are not entirely shared by John and his communities. The writer of Revelation possesses high ascetic and sectarian demands which keep him away, not only from the society at large but from the brethren who do not share the same opinion. John sees the world immersed into a conflict between the Dragon and the Lamb, a conflict which will be conquered with the participation of the 144.000 warriors through the practice of martyrdom. This ideology of the holy war inserts in the Book of Revelation the potential of isolating, in a sectarian way, the audience of the society and of other religious groups.(AU)